Development of Dagestan poetry in 1970–1980s: historical and gender aspects - G. Sh. Kaymarazov; L. G. Kaymarazova (Вестник Майкопского государственного технологического университета, 2025)
Abstract. The relevance. Due to the unflagging interest to the history of artistic culture of the peoples of the Russian Federation historical and gender aspects of the development of multinational Dagestani poetry in 1970-1980s have been covered in the article. The principles of historicism and scientific objectivity, traditional methods of historical research and interdisciplinary research methods, including literary studies have been considered. The investigated period, on the one hand, was characterized by further centralization of governance in the country and strengthening of ideological control over the sphere of culture and its important branch – literature, on the other hand, the emergence of new ideological guidelines associated with the beginning of «perestroika». The scientific novelty of the research consists in the gender approach to interpreting the content of poetic works of Dagestani writers in the context of the Russian historical and literary process in the studied twenty years, in the characteristics of the works of Dagestani poets from the standpoint of reflecting in them themes of women, as well as themes of love, family traditions and values, education of the younger generation in the spirit of love for the Motherland. The authors have summarized the data on the gender composition of the creative collective of poets of Dagestan, taking into account national representation, drew conclusions about the increasing contribution of Dagestani poetesses to the development of poetry of the multinational region, characterized the prospects and scope of application of the research results.